The symbolic and utilitarian facets of pacifiers according to mothers - Sertório, Sonia Cristina Masson; Silva, Isilia Aparecida (Revista de Saúde Pública, 2005)
OBJECTIVE: Despite governmental initiatives that control, discourage and even prohibit the divulgation of the usage of dummies and pacifiers in maternity wards, the frequency of pacifier use by Brazilian children is still high. In light of this phenomenon, the aim of the present study was to investigate the social representations of the pacifier constructed by mothers whose children used pacifiers. METHODS: The present study is based on the conceptual framework of social representations, proposed by Moscovici. We studied women who gave birth at a teaching hospital in the city of Sao Paulo that prohibits the use of pacifiers during hospital admission. We conducted non-structured individual interviews that were transcribed in full and organized for analysis according to the collective subject discourse method. RESULTS: Our results indicate maternal representations that the pacifier "symbolizes the child," that is "is a tranquilizer for the child and an aid for the mother," and that "its use is inherited from generation to generation". CONCLUSIONS: Pacifiers are an alternative for the mother for comforting and hushing her child in moments of agitation or for when the mother is not able to tend to the child in a direct and continuous manner.